Comparative modal analysis of cantilever beam made of biocomposites using finite element analysis. (2022) - Pankaj,; Kant, Suman; Jawalkar, C.S.
Abstract: Natural fiber reinforced polymer composites are attracting many scientist and researcher across the world to develop low cost, biodegradable and environmentally friendly materials. Therefore, for the present study a cantilever beam prepared from natural fiber reinforced polymer composite has been selected for the finite element analysis. We have considered nettle/polyester and chicken feather/epoxy composites material for the development of a cantilever beam to analyze the vibration behavior using ANSYS. The modal analysis was carried out to predict the natural frequencies and mode shapes of the beam structure. During the study natural frequencies and mode shapes of the nettle/polyester and chicken feather/epoxy beam structures were compared with each other. It is found from this analytical study that the natural frequencies of nettle/polyester cantilever were more than chicken feather/epoxy. The natural frequency of nettle/polyester and chicken feather/epoxy cantilever beam varies from 30.196 Hz to 1031.7 Hz and 16.371 Hz to 559.84 Hz respectively. These result obtained through modal analysis will be beneficial for engineers and scientists to find safe working condition while developing mechanical and structural member with these composite materials.